An insight into optical metrology in manufacturing - Shimizu, Yuki; Chen, Liang-Chia; Kim, Dae Wook; Chen, Xiuguo; Li, Xinghui; Matsukuma, Hiraku (Measurement science & technology, 2021)
Optical metrology is one of the key technologies in today's manufacturing industry. In this article, we provide an insight into optical measurement technologies for precision positioning and quality assessment in today's manufacturing industry. First, some optical measurement technologies for precision positioning are explained, mainly focusing on those with a multi-axis positioning system composed of linear slides, often employed in machine tools or measuring instruments. Some optical measurement technologies for the quality assessment of products are then reviewed, focusing on technologies for form measurement of products with a large metric structure, from a telescope mirror to a nanometric structure such as a semiconductor electrode. Furthermore, we also review the state-of-the-art optical technique that has attracted attention in recent years, optical coherence tomography for the non-destructive inspection of the internal structures of a fabricated component, as well as super-resolution techniques for improving the lateral resolution of optical imaging beyond the diffraction limit of light. This review article provides insights into current and future technologies for optical measurement in the manufacturing industry, which are expected to become even more important to meet the industry's continuing requirements for high-precision and high-efficiency machining.